Principle of Islamic neighborhood planning in order to create a better neighborhood community - Safee, Fatimatul Azadiah; Mohd Yunos, Mohd Yazid; Mohd Isa, Nor Kalsum; Mohamed Kamil, Safwah; Hussain, Mohd Amirul (American-Eurasian Network for Scientific Information, 2016)
The design of neighborhood community are important is to achieve social unity and harmony among others are strongly encouraged for city development. The balancing elements of physical, social and environment is importance to forming a city. Nowadays, many people become individually and personally, especially in communities involving of their local neighborhoods. Traditional Islamic teachings and traditions involve guideline that has direct application in the domestic sphere. In order to move towards sustainable Islamic urban planning in Malaysia, the formation of city planning must be firmly balance not only physically but also the social aspect. This study will identify an Islamic neighborhood principle to be assimilated into Islamic city Planning in Malaysia. To identify the principles of Islamic neighborhood principles, a qualitative method research that involves content analysis is the most suitable approach to be employed in this study. By the end of the research, this study will reveal the principle of neighborhood planning based on Islamic perspective. Thus, this study suggested that good neighborhood planning practices could contribute and formulate for good urban form and enhance a better quality of life.